Peran Variasi Produk, Harga, dan Layanan dalam Membangun Loyalitas Pelanggan di Pasar Kosmetik Semarang - Irawati, Anggita; Widyartati, Penta; Surati, Aprilia (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
Customer loyalty is a condition where customers consistently make repeat purchases, hold a positive attitude towards a brand, are committed to that brand, and intend to continue purchasing in the future. This study aims to analyze the influence of product completeness, price perception, and service quality on customer loyalty at Semarang Cosmetic Store. The population in this study comprises consumers or customers of Semarang Cosmetic Store, with an unknown total number. The sample size was calculated using Cochran's formula, resulting in a sample of 97 customers. The sampling technique used is non-probability sampling, specifically incidental sampling. The independent variables in this study include product completeness (X1), price perception (X2), and service quality (X3), while the dependent variable is customer loyalty (Y). Data were collected using a questionnaire that has been tested for validity and reliability. The data analysis technique used in this study is multiple regression, with calculations assisted by the SPSS application. The results of the analysis show that the t-value for the product completeness variable is 3.849, which is greater than the t-table value of 1.985, with a significance level of 0.000. This indicates that the product completeness variable has a positive and significant influence on customer loyalty. Furthermore, the t-value for the price perception variable is 3.960, also greater than the t-table value of 1.985, with a significance level of 0.000, indicating that price perception has a positive and significant influence on customer loyalty. The t-value for the service quality variable is 4.495, greater than the t-table value of 1.985, with a significance level of 0.000, indicating that service quality also has a positive and significant influence on customer loyalty. The coefficient of determination (R Square) of 0.855 indicates that the variables of product completeness, price perception, and service quality collectively explain 85.5% of the variation in customer loyalty. Based on these findings, it is recommended that the Cosmetic Store effectively manage product completeness to meet customer expectations, as this is a key factor in competition among cosmetic stores, where a well-rounded product offering can attract customer interest. The store should maintain the currently favorable price perception and is encouraged to implement customer loyalty programs, such as purchase discounts and other incentives..